Evolution of surgical modalities in the management of rhinophyma: our experience. Issue 2 (February 2021) - Goh, M.; Gönen, Z.B.; Sayan, A.; Ilankovan, V.
Abstract: Rhinophyma is a progressive disease of the nose, which is characterised by skin thickening and sebaceous hyperplasia. Patients with rhinophyma are often stigmatised due to worsening disfigurement of their nose. This can also result in functional impairment such as reduced nasal patency. Severe cases of rhinophyma are best managed with varied surgical interventions, as there is no clear 'gold standard' treatment that has been described. We present our experiences in the management of rhinophyma and the evolution of treatment modalities that have been employed over a nine-year period.